Targeting the Aryl Hydrocarbon Receptor With Indole-3-Aldehyde Protects From Vulvovaginal Candidiasis via the IL-22-IL-18 Cross-Talk - Borghi, Monica; Pariano, Marilena; Solito, Valentina; Puccetti, Matteo; Bellet, Marina M.; Stincardini, Claudia; Renga, Giorgia; Vacca, Carmine; Sellitto, Federica; Mosci, Paolo; Brancorsini, Stefano; Romani, Luigina; et al. (Frontiers in Immunology, 2019)
Vulvovaginal candidiasis (VVC) is a common mucosal infection caused by Candida spp., most frequently by Candida albicans, which may become recurrent and severely impacting the quality of life of susceptible women. Although it is increasingly being recognized that mucosal damage is mediated by an exaggerated inflammatory response, current therapeutic approaches are only based on antifungals that may relieve the symptomatology, but fail to definitely prevent recurrences. The unrestrained activation of the NLRP3 inflammasome with continuous production of IL-1β and recruitment of neutrophils is recognized as a pathogenic factor in VVC. We have previously shown that IL-22 is required to dampen pathogenic inflammasome activation in VVC via the NLRC4/IL-1Ra axis. However, IL-22 also regulates IL-18, a product of the inflammasome activity that regulates IL-22 expression. Here we describe a cross-regulatory circuit between IL-18 and IL-22 in murine VVC that is therapeutically druggable. We found that IL-18 production was dependent on IL-22 and NLRC4, and that IL-18, in turn, contributes to IL-22 activity. Like in IL-22 deficiency, IL-18 deficiency was associated with an increased susceptibility to VVC and unbalanced Th17/Treg response, suggesting that IL-18 can regulate both the innate and the adaptive responses to the fungus. Administration of the microbial metabolite indole-3-aldehyde, known to stimulate the production of IL-22 via the aryl hydrocarbon receptor (AhR), promoted IL-18 expression and protection against Candida infection. Should low levels of IL-18 be demonstrated in the vaginal fluids of women with recurrent VVC, targeting the AhR/IL-22/IL-18 pathway could be exploited for future therapeutic approaches in VVC. This study suggests that a deeper understanding of the mechanisms regulating inflammasome activity may lead to the identification of novel targets for intervention in VVC.